ELASTISITAS KREDIT TERHADAP DANA PIHAK KETIGA DAN KINERJA KEUANGAN PADA BANK PERKREDITAN RAKYAT DI KALIMANTAN BARAT - B01109097, Wahyuni (Jurnal Pembangunan dan Pemerataan, 2013)
The title of this research is "The Elasticity 0f Credit at the Third Party Funds And Financial Performance of Rural Banks in West Kalimantan". The purpose of this research is to "determine the elasticity of credit to deposit and analyze the financial performance of rural banks in West Kalimantan". The method used in this study is the method of multiple linear regression and qualitative analysis, using secondary data obtained from the monthly financial statements of Bank Indonesia. The results showed that the elasticity of savings and deposits elasticity is inelastic because the value of savings and time deposits of less than 1%. While the financial performance of rural banks in the West Kalimantan generally better in 2011 whereby each of the indicators of financial performance as seen from the CAR ratio, ROA and NPL managed to exceed the standards set, except LDR. Keywords: Loans total, deposits, and Financial Performance of BPR